2014
DOI: 10.3201/eid2005.130948
|View full text |Cite
|
Sign up to set email alerts
|

Carriage Rate and Effects of Vaccination after Outbreaks of Serogroup C Meningococcal Disease, Brazil, 2010

Abstract: Polysaccharide vaccine did not affect carriage nor interrupt transmission of an epidemic strain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 26 publications
0
41
1
Order By: Relevance
“…Carriage rates in adolescents, in a study performed 2 years after the initiation of the infant immunization program, showed a prevalence of 10%, where serogroups were identified, serogroup C was the most common (1.32%), followed by serogroups B (0.99%), E (0.74%), Y (0.49%), and W (0.25%) [37]. Although plain PSVs offered protection against disease, they did not prevent acquisition of carriage of MenC in the 2010 outbreaks [38], which is why only conjugate vaccines are now used to control outbreaks.…”
Section: Latin Americamentioning
confidence: 99%
“…Carriage rates in adolescents, in a study performed 2 years after the initiation of the infant immunization program, showed a prevalence of 10%, where serogroups were identified, serogroup C was the most common (1.32%), followed by serogroups B (0.99%), E (0.74%), Y (0.49%), and W (0.25%) [37]. Although plain PSVs offered protection against disease, they did not prevent acquisition of carriage of MenC in the 2010 outbreaks [38], which is why only conjugate vaccines are now used to control outbreaks.…”
Section: Latin Americamentioning
confidence: 99%
“…This could be due to the short-term persistence of circulating antibodies and immune response quality. Conversely, MCC vaccination programs not only induced a stronger long-term protection, but also were able to prevent meningococcal carriage [82]. These findings support the use of MCC vaccine instead of polysaccharide A/C vaccine in case of MenC outbreaks.…”
Section: Serogroup C Meningococcal Disease Epidemiologymentioning
confidence: 49%
“…Only a limited number of studies have evaluated the putative effect of the vaccination campaign on meningococcal transmission in Brazil. A recent investigation conducted by Sáfadi et al [82] confirmed that meningococcal A/C polysaccharide vaccine did not affect MenC carriage or block meningococcal transmission to susceptible individuals. This could be due to the short-term persistence of circulating antibodies and immune response quality.…”
Section: Serogroup C Meningococcal Disease Epidemiologymentioning
confidence: 79%
See 2 more Smart Citations